Islamic Peace Ethics Legitimate and Illegitimate Violence in Contemporary Islamic Thought - Shadi, Heydar (Studien zur Friedensethik, 2017)
This book addresses the arguments of contemporary Muslim thinkers regarding war and peace. It takes into account the confessional, geographical and ideological diversity of Islamic peace ethics and includes papers on peace ethics by different groups and scholars who represent both the Sunni and Shi